Comparison of systemic trimethoprim-sulfadimethoxine treatment and intrauterine ozone application as possible therapies for bacterial endometritis in equine practice - Köhne, Martin; Hofbauer, Lisa; Böttcher, Denny; Tönissen, Anna; Hegger, Anna; Görgens, Alexandra; Ulrich, Reiner; Sieme, Harald (Frontiers in Veterinary Science, 2023)
Bacterial endometritis is one of the major problems in equine reproduction and usually treated with antimicrobial drugs. The study aimed to compare the effects of intrauterine ozone application and systemic antibiotic treatment (trimethoprim-sulfadimethoxine) on intrauterine bacterial growth and possible side effects on the endometrium in a clinical setting. Mares (n=30) with signs of endometritis (positive uterine bacterial culture and cytological findings) were assigned randomly to different treatments: intrauterine insufflation of an ozone-air-mix (240 ml, 80 µg ozone/ml) twice at a 48h-interval (Ozone; n=10), systemic antibiotic therapy with trimethoprim-sulfadimethoxine (30 mg/kg, p.o., twice daily) for five days (TMS; n=10), or intrauterine insufflation of air (240 ml, sterile-filtered) twice at a 48h-interval (Air; n=10). Endometrial biopsy for histological examination was obtained before the treatment. A control examination, including transrectal ultrasound, bacterial culture, cytological evaluation, and biopsy, was performed 7 days after the last treatment. Overall bacterial growth was reduced in every group after the treatment (p<0.05), irrespective of the therapy (Ozone: 4/9 (positive culture after treatment/number of mares), TMS: 3/10 and Air: 6/10; p>0.05). However, Ozone and TMS (p<0.05) were more effective in reducing growth of gram-negative bacteria as compared to Air (p>0.05). No effects on the number of polymorphonuclear granulocytes (cytology) were observed (p>0.05). Histological examination revealed no differences among groups. In conclusion, trimethoprim-sulfadimethoxine and intrauterine ozone insufflation are safe treatment options for bacterial endometritis in mares but the efficacy of both treatments in reducing bacterial growth did not result in a complete absence of intrauterine bacterial growth.